A method for preparing a phosphine-functionalized metal-organic framework supported cobalt-based catalytic material
Patent Information
- Application Number
- CN202611386051.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这类基于简单负载策略构建的MOF催化体系通常缺乏稳定而明确的金属配位结构,金属活性物种多以物理吸附或弱配位形式存在
1、本发明将膦功能化金属有机框架(UiO-66-NH2-PPh3)作为载体负载乙酰丙酮钴,成功构建了用于烯烃氢甲酰化反应的多相钴基催化体系。
Smart Images

Figure CN122912925A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydroformylation technology, and more particularly to a method for preparing a cobalt-based catalytic material supported on a phosphine-functionalized metal-organic framework. Background Technology
[0002] Hydroformylation of olefins refers to the process by which olefins react with syngas (CO / H2) under transition metal catalysis to form aldehydes, which have one more carbon atom than the original olefin. This reaction boasts 100% atom economy and is one of the largest industrial applications of homogeneous catalysis to date. More than 10 million tons of aldehydes are produced annually through this process. These aldehydes can be further converted into high-value-added chemicals such as alcohols, acids, esters, and amines, finding wide applications in plasticizers, detergents, surfactants, pharmaceuticals, and fine chemicals (Chem. Rev., 2012, 112, 5675-5732; Eur. J. Org. Chem., 2012, 6309-6320).
[0003] Currently, industrial hydroformylation processes mainly employ rhodium (Rh) or cobalt (Co)-based homogeneous catalytic systems. Among these, Rh-based catalysts dominate due to their high activity and selectivity under mild conditions. In contrast, cobalt metal is abundant in the Earth's crust and inexpensive, offering a significant cost advantage. Although the intrinsic activity of Co-based catalytic systems in hydroformylation reactions is lower than that of the precious metal Rh, and their industrial applications have long been limited by relatively harsh reaction conditions, the cobalt system possesses unique reaction characteristics. For example, under specific conditions, it can directly catalyze the hydroformylation-hydrogenation tandem reaction of olefins, achieving a one-pot synthesis from olefins to high-value-added alcohols, thereby simplifying the process (J. Am. Chem. Soc., 2022, 144(42): 19219-19224).
[0004] However, traditional homogeneous catalytic systems all face common challenges such as difficulty in separating the catalyst from the product, loss of precious metals, and difficulty in recycling the catalyst. Especially when high-carbon olefins are used as reaction substrates, the high boiling point of the product makes homogeneous catalysts more prone to deactivation or metal agglomeration during high-temperature separation and distillation (Chem. Sus. Chem., 2018, 11, 2310-2314). Therefore, developing heterogeneous catalytic materials with high activity, high selectivity, and easy separation and recovery has become an important research direction in the field of olefin hydroformylation.
[0005] In recent years, metal-organic frameworks (MOFs) have attracted widespread attention in the field of heterogeneous catalysis due to their highly ordered pore structure, ultra-high specific surface area, and tunable chemical environment. However, these MOF catalytic systems, constructed based on simple loading strategies, typically lack stable and well-defined metal coordination structures, with active metal species often existing in physisorption or weak coordination forms. Under a CO / H2 reaction atmosphere, these metal species are prone to carbonylation or migration, leading to a decline in catalyst stability and recyclability.
[0006] Based on this, researchers proposed the concept of phosphine-functionalized metal-organic frameworks (P-MOFs). This strategy involves introducing phosphine ligands into the MOF framework and forming stable metal-phosphine coordination structures with transition metals, thereby constructing well-defined metal-phosphine active centers within their pores. Compared to traditional supported catalysts, P-MOFs can not only regulate the coordination environment of the metal centers at the molecular scale, but also utilize the confinement effect generated by the MOF pores to modulate substrate diffusion behavior and the stability of reaction intermediates, thus achieving synergistic regulation of catalytic activity and selectivity. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a simple and mild method for preparing cobalt-based catalytic materials supported by phosphine-functionalized metal-organic frameworks.
[0008] To address the above problems, the present invention provides a method for preparing a cobalt-based catalytic material supported by a phosphine-functionalized metal-organic framework, comprising the following steps: (1) Preparation of phosphine-functionalized metal-organic framework carrier materials: 2-Aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine were dissolved in N,N-dimethylformamide (DMF) solvent and stirred until completely dissolved. Acetic acid was then added and mixed thoroughly. The resulting mixture was transferred to a high-pressure hydrothermal reactor lined with polytetrafluoroethylene, sealed, and reacted at 120°C for 24 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was separated by centrifugation and washed. The resulting pale yellow powder was dried under vacuum at 90°C to constant weight, yielding the phosphine-functionalized metal-organic framework carrier material, named UiO-66-NH2-PPh3. (2) Preparation of cobalt-based catalytic materials supported by phosphine-functionalized metal-organic frameworks: The UiO-66-NH2-PPh3 was added to a toluene solvent containing cobalt acetylacetone, stirred and ultrasonically dispersed to ensure uniformity, and then the mixture was refluxed and stirred in an oil bath at 80°C for 24 hours for loading. After the reaction was completed, the mixture was naturally cooled to room temperature, and the product was separated by centrifugation and washed. The resulting gray powder was dried under vacuum at 80°C to constant weight to obtain the phosphine-functionalized metal-organic framework supported cobalt-based catalytic material, named Co / UiO-66-NH2-PPh3.
[0009] The synthesis process of this phosphine-functionalized metal-organic framework-supported cobalt-based catalytic material is as follows: In step (1), the molar ratio of 2-aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine is 3:3.3:1.5.
[0010] In step (1), the volume ratio of acetic acid to N,N-dimethylformamide is 18:50; the ratio of 2-aminoterephthalic acid to N,N-dimethylformamide is 10.8 g / mL.
[0011] In step (2), the mass ratio of cobalt acetylacetone to UiO-66-NH2-PPh3 is 1:(2~3).
[0012] In step (2), the concentration of the toluene solvent containing cobalt acetylacetonate is 3.6 mg / mL.
[0013] A phosphine-functionalized metal-organic framework supported cobalt-based catalytic material prepared by the method described above.
[0014] The cobalt metal is loaded onto the UiO-66-NH2-PPh3 support in a highly dispersed form, and the theoretical loading of cobalt metal is 5 wt%.
[0015] The application of cobalt-based catalytic materials supported by phosphine-functionalized metal-organic frameworks as described above in the hydroformylation reaction of olefins.
[0016] The olefin is C4~C6. 12 Terminal olefins, cyclic olefins, or aromatic olefins.
[0017] The conditions for the hydroformylation reaction are: a reaction temperature of 80-170℃, a synthesis gas pressure of 2-6MPa, and a reaction time of 2-24h; the reaction solvent is one of toluene, DMF, dioxane, or acetonitrile; and the synthesis gas is a mixture of CO and H2 in a volume ratio of 1:1 or 1:2.
[0018] Compared with the prior art, the present invention has the following advantages: 1. This invention uses a phosphine-functionalized metal-organic framework (UiO-66-NH2-PPh3) as a support to load cobalt acetylacetone, and successfully constructs a heterogeneous cobalt-based catalytic system for olefin hydroformylation reaction.
[0019] 2. By introducing triphenylphosphine in situ into the MOF framework, this invention can, on the one hand, utilize the MOF channels to provide a physical confinement effect for the active metal center, thereby inhibiting metal aggregation and loss; on the other hand, the phosphine group has a strong coordination effect with cobalt metal, which can regulate the electronic and spatial structure of the active center, providing homogeneous reactivity and selectivity.
[0020] 3. This invention introduces phosphine ligands into the MOF structure in one step using a solvothermal method. The interaction between phosphine and zirconium clusters effectively avoids the problem of oxidation and deactivation of free phosphine ligands during the reaction process. At the same time, it provides abundant anchoring sites for cobalt species, achieving high dispersion of cobalt species on the support surface and significantly improving the utilization efficiency of active sites.
[0021] 4. The present invention has mild reaction conditions, simple synthesis process, easy operation, and easy-to-achieve equipment requirements and reaction conditions, making it suitable for large-scale production.
[0022] 5. The catalyst obtained by the method of this invention has a stable structure and properties, exhibits excellent catalytic activity in the hydroformylation of olefins, and shows significantly reduced loss of cobalt metal active components and structural damage during the reaction. Compared with other reported heterogeneous hydroformylation catalysts, it has obvious performance and structural advantages, and greatly saves costs. Attached Figure Description
[0023] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0024] Figure 1 Aberration-corrected electron microscopy image and elemental analysis of the cobalt-based heterogeneous catalytic material supported on a phosphine-functionalized metal-organic framework prepared in Example 1 of this invention.
[0025] Figure 2 The images show the XRD patterns of the cobalt-based heterogeneous catalytic materials supported on phosphine-functionalized metal-organic frameworks prepared in Examples 1-4 of this invention.
[0026] Figure 3 XPS image of the cobalt-based heterogeneous catalytic material supported on a phosphine-functionalized metal-organic framework prepared in Example 1 of this invention.
[0027] Figure 4 This is a comparison chart of the performance of the catalytic materials prepared in Example 1 and Comparative Examples 1-3 of the present invention.
[0028] Figure 5 This is a comparison chart of the cycle performance of the catalytic materials prepared in Example 1 and Comparative Example 3 of the present invention. Detailed Implementation
[0029] This invention first prepares a phosphine-functionalized metal-organic framework (MOF) support, UiO-66-NH2-PPh3, by reacting 2-aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine in a mixed solvent of N,N-dimethylformamide and acetic acid using a solvothermal method. Subsequently, cobalt is loaded onto the MOF framework using the strong interaction between the metal and phosphine to obtain a Co / UiO-66-NH2-PPh3 catalytic material. The specific process is as follows: A method for preparing a cobalt-based catalytic material supported by a phosphine-functionalized metal-organic framework includes the following steps: (1) Preparation of phosphine-functionalized metal-organic framework carrier materials: 2-Aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine were dissolved in N,N-dimethylformamide (DMF) solvent and stirred until completely dissolved. Acetic acid was then added and mixed thoroughly. The molar ratio of 2-aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine was 3:3.3:1.5; the volume ratio (v / v, mL) of acetic acid to N,N-dimethylformamide was 18:50; and the ratio of 2-aminoterephthalic acid to N,N-dimethylformamide was 10.8 g / mL. The resulting mixture was transferred to a polytetrafluoroethylene-lined high-pressure hydrothermal reactor, sealed, and reacted at 120°C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was separated by centrifugation and washed repeatedly with DMF, methanol, and dichloromethane. The resulting pale yellow powder was dried under vacuum at 90°C to constant weight, yielding the phosphine-functionalized metal-organic framework carrier material, named UiO-66-NH2-PPh3.
[0030] (2) Preparation of cobalt-based catalytic materials supported by phosphine-functionalized metal-organic frameworks: UiO-66-NH2-PPh3 was added to a toluene solvent containing cobalt acetylacetonate at a concentration of 3.6 mg / mL, with a mass ratio (g / g) of cobalt acetylacetonate to UiO-66-NH2-PPh3 of 1:(2~3). After stirring and ultrasonication to ensure uniform dispersion, the mixture was refluxed and stirred in an oil bath at 80℃ for 24 h for loading. After the reaction was completed, the mixture was naturally cooled to room temperature, and the product was separated by centrifugation and washed repeatedly with toluene and anhydrous ethanol. The resulting gray powder was dried under vacuum at 80℃ to constant weight, yielding the phosphine-functionalized metal-organic framework-supported cobalt-based catalyst, named Co / UiO-66-NH2-PPh3.
[0031] In this phosphine-functionalized metal-organic framework supported cobalt-based catalytic material, cobalt metal is supported in a highly dispersed form on the UiO-66-NH2-PPh3 support, and the theoretical loading of cobalt metal is 5 wt%.
[0032] Application of this phosphine-functionalized metal-organic framework supported cobalt-based catalytic material in the hydroformylation reaction of olefins. Wherein: the olefin is C4~C6. 12 Terminal olefins, cyclic olefins, or aromatic olefins.
[0033] The conditions for hydroformylation are: reaction temperature of 80-170℃, syngas pressure of 2-6MPa, and reaction time of 2-24h; the reaction solvent is one of toluene, DMF, dioxane, or acetonitrile; and the syngas is a mixture of CO and H2 in a volume ratio (mL / mL) of 1:1 or 1:2.
[0034] Example 1 Synthesis of Co / UiO-66-NH2-PPh3 heterogeneous catalytic material (theoretical cobalt metal loading is 5 wt%): (1) 2-Aminoterephthalic acid (3 mmol, 0.54 g), zirconium tetrachloride (3.3 mmol, 0.77 g), and triphenylphosphine (1.5 mmol, 0.39 g) were dissolved in 50 mL of N,N-dimethylformamide (DMF) solvent. After stirring until completely dissolved, 18 mL of acetic acid was added, and the mixture was ultrasonically dispersed for 10 min. The resulting mixture was transferred to a 100 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene, sealed, and placed in an oven at 120 °C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the product was collected by centrifugation. The product was washed three times each with DMF, methanol, and dichloromethane. The pale yellow powder was dried under vacuum at 90 °C for 12 h to obtain the UiO-66-NH2-PPh3 support.
[0035] (2) Weigh 500 mg of UiO-66-NH2-PPh3 support and add it to 60 mL of toluene solvent. Stir and sonicate for 10 min each to ensure uniform dispersion. Add cobalt acetylacetonate (0.85 mmol, 218 mg) to the above mixture, stir at room temperature for 30 min, and then transfer to an 80 °C oil bath for reflux and stirring for 24 h. After the reaction is complete, allow it to cool naturally to room temperature, centrifuge to separate the product, and wash it three times each with toluene and anhydrous ethanol. Dry the gray powder under vacuum at 80 °C for 12 h to obtain the Co / UiO-66-NH2-PPh3 catalyst.
[0036] The Co / UiO-66-NH2-PPh3 catalyst prepared in Example 1 was characterized by electron microscopy, XRD, and XPS, respectively. The results are as follows: Figures 1-3As shown. Electron microscopy results show that the catalyst after metal loading still maintains an octahedral morphology with a particle size in the range of 200~400nm, indicating that the doping of phosphine ligands has no significant effect on the morphology of UiO-66. In addition, aberration-corrected electron microscopy and elemental analysis show that Co metal mainly exists in the form of single atoms and clusters, and is uniformly distributed on the catalyst surface. In the XRD spectrum, the sample shows diffraction peaks near 2θ = 7.4°, 8.5° and 25.7°, which are attributed to the (111), (200) and (600) crystal planes of the UiO-66 metal-organic framework, respectively. No characteristic peaks belonging to Co metal or cobalt oxides were observed in the spectrum, indicating that the cobalt species are highly dispersed. XPS analysis shows that the spectrum of Co 2p electrons presents two main peaks, located at 781.4eV (Co2p 3 / 2 ) and 796.9 eV (Co 2p 1 / 2 ), and two satellite peaks, which can be attributed to Co 2+ Coordination between ions and cobalt ions and phosphine groups in the framework.
[0037] Catalyst evaluation: 50 mg of catalyst sample was added to 5 mL of toluene solution containing 10 mmol (1.12 g). After sealing the reactor, it was purged three times with syngas (CO / H2 = 1:1), and then purged with syngas at 5 MPa. The reactor was placed in a heating module preheated to 160 °C and stirred for 10 h. After the reaction was complete, the reactor was cooled to room temperature and the pressure was slowly released. After the reaction was complete, the reactor was cooled in an ice bath, the remaining gas was slowly released, and hexadecane was added as an internal standard. The liquid products were qualitatively analyzed using a gas chromatograph (Agilent 7890 GC) equipped with a flame ionization detector (FID) and an SE-54 column (30 m × 0.25 mm × 0.25 μm). Conversion and yield were calculated using the internal standard method and NMR quantification.
[0038] Comparative Example 1 Synthesis of Co / UiO-66 heterogeneous catalytic material (theoretical cobalt metal loading is 5 wt%): (1) Terephthalic acid (3 mmol, 0.49 g) and zirconium tetrachloride (3.3 mmol, 0.77 g) were dissolved in 50 mL of N,N-dimethylformamide (DMF) solvent. After stirring until completely dissolved, 18 mL of acetic acid was added, and the mixture was ultrasonically dispersed for 10 min. The resulting mixture was transferred to a 100 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene, sealed, and placed in an oven at 120 °C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the product was collected by centrifugation. The product was washed three times each with DMF, methanol, and dichloromethane. The white solid was dried under vacuum at 90 °C for 12 h to obtain the UiO-66 support.
[0039] (2) Weigh 500 mg of the obtained UiO-66 support and add it to 60 mL of toluene solvent. Stir and sonicate for 10 min each to ensure uniform dispersion. Add the Co(acac)2 precursor (0.85 mmol, 218 mg) to the above mixture, stir at room temperature for 30 min, and then transfer to an 80 °C oil bath for reflux and stirring for 24 h. After the reaction is complete, allow it to cool naturally to room temperature, centrifuge to separate the product, and wash it three times each with toluene and anhydrous ethanol. Dry the gray powder under vacuum at 90 °C for 12 h to obtain the Co / UiO-66 catalyst.
[0040] The catalyst evaluation and product analysis were the same as in Example 1.
[0041] Comparative Example 2 Synthesis of Co / UiO-66-NH2 heterogeneous catalytic material (theoretical cobalt metal loading is 5 wt%): (1) 2-Aminoterephthalic acid (3 mmol, 0.54 g) and zirconium chloride (3.3 mmol, 0.77 g) were dissolved in 50 mL of N,N-dimethylformamide (DMF) solvent. After stirring until completely dissolved, 18 mL of acetic acid was added, and the mixture was ultrasonically dispersed for 10 min. The resulting mixture was transferred to a 100 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene, sealed, and placed in an oven at 120 °C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the product was collected by centrifugation. The product was washed three times each with DMF, methanol, and dichloromethane. The pale yellow solid was dried under vacuum at 90 °C for 12 h to obtain the UiO-66-NH2 support.
[0042] (2) Weigh 500 mg of the obtained UiO-66-NH2 support and add it to 60 mL of toluene solvent. Stir and sonicate for 10 min each to ensure uniform dispersion. Add the Co(acac)2 precursor (0.85 mmol, 218 mg) to the above mixture, stir at room temperature for 30 min, and then transfer to an 80 °C oil bath for reflux and stirring for 24 h. After the reaction is complete, allow it to cool naturally to room temperature, centrifuge to separate the product, and wash it three times each with toluene and anhydrous ethanol. Dry the gray powder under vacuum at 90 °C for 12 h to obtain the Co / UiO-66-NH2 catalyst.
[0043] Catalyst evaluation and product analysis were the same as in Example 1.
[0044] Comparative Example 3 Synthesis of Co(acac)2 / SBA-15-PPh3 heterogeneous catalyst (theoretical cobalt metal loading is 5 wt%): (1) Pre-activated SBA-15 (1.0 g) was added to a flask containing 80 ml of toluene solvent, stirred and sonicated for 10 min each to ensure uniform dispersion. Under Ar atmosphere protection, vinyltriethoxysilane (10 mmol, 1.9 g) was added to the above mixture, stirred at room temperature for 30 min, and then transferred to an oil bath at 110 °C for reflux and stirring for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, centrifuged to separate the product, and washed three times each with toluene and anhydrous ethanol. The white solid was dried under vacuum at 100 °C for 12 h to obtain SBA-15-VTES.
[0045] (2) Weigh 500 mg of SBA-15-VTES and add it to 40 ml of toluene solvent. Stir and sonicate for 30 min each time to ensure uniform dispersion. Under Ar atmosphere protection, add 15 ml of toluene solution containing vinyl diphenylphosphine (3 mmol, 0.864 g) and azobisisobutyronitrile (0.15 mmol, 25 mg) dropwise to the above reaction solution. After stirring at room temperature for 30 min, transfer to a 90 °C oil bath and reflux for 24 h. After the reaction is complete, allow to cool to room temperature naturally, centrifuge to separate the product, and wash three times each with toluene and anhydrous ethanol. Dry the light yellow solid under vacuum at 100 °C for 12 h to obtain the SBA-15-PPh2 support.
[0046] (3) Weigh 500 mg of the obtained SBA-15-PPh2 support and add it to 60 mL of toluene solvent. Stir and sonicate for 10 min each to ensure uniform dispersion. Add the Co(acac)2 precursor (0.85 mmol, 218 mg) to the above mixture, stir at room temperature for 30 min, and then transfer to an 80 °C oil bath for reflux and stirring for 24 h. After the reaction is complete, allow it to cool naturally to room temperature, centrifuge to separate the product, and wash it three times each with toluene and anhydrous ethanol. Dry the gray powder under vacuum at 90 °C for 12 h to obtain the Co / SBA-15-PPh2 catalyst.
[0047] The catalyst evaluation and product analysis were the same as in Example 1.
[0048] Depend on Figure 4It can be seen that the catalysts prepared in Example 1 and Comparative Examples 1-3 exhibit different reaction performances in the hydroformylation reaction. The four catalysts showed almost identical conversion rates of octene, approaching complete conversion. Among them, the phosphine-functionalized Co / UiO-66-NH2-PPh3 catalyst exhibited the best performance, with a total yield of aldehydes and alcohols reaching 95.6%, while the sum of isomerization and hydrogenation products was only 4.3%. In contrast, although both Co / UiO-66 and Co / UiO-66-NH2 catalysts showed excellent octene conversion, their oxidation product yields were lower. The comparison revealed that the phosphine-functionalized Co / UiO-66-NH2-PPh3 catalyst, due to the presence of phosphine functional sites, exhibited the best activity and linear aldehyde selectivity. Furthermore, while the infinite-domain effect of Co / SBA-15-PPh2 showed high activity and selectivity, the lack of a unique physical confinement environment provided by the regular pores of the MOF resulted in low selectivity for linear aldehydes.
[0049] In Examples 2-10, the hydroformylation reaction performance under different reaction temperatures and syngas pressures was evaluated using the catalyst from Example 1 as an example.
[0050] Example 2 Catalyst evaluation: In Example 2, except that the reactor temperature was heated to 140°C, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0051] Example 3 Catalyst evaluation: In Example 3, except that the reactor temperature was heated to 150°C, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0052] Example 4 Catalyst evaluation: In Example 4, except that the reactor temperature was heated to 170°C, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0053] Example 5 Catalyst evaluation: In Example 5, except that the syngas pressure (CO:H2 = 1:1) was increased to 6 MPa, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0054] Example 6 Catalyst evaluation: In Example 6, except that the syngas pressure (CO:H2 = 1:1) was increased to 4 MPa, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0055] Example 7 Catalyst evaluation: In Example 7, except that the syngas pressure (CO:H2 = 1:1, 5MPa) was changed to the syngas pressure (CO:H2 = 2:1, 5MPa), the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0056] Example 8 Catalyst evaluation: In Example 8, except that the syngas pressure (CO:H2 = 1:1, 5 MPa) was changed to the syngas pressure (CO:H2 = 2:1, 6 MPa), the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0057] Example 9 Catalyst evaluation: In Example 9, except that the syngas pressure (CO:H2 = 1:1, 5MPa) was changed to the syngas pressure (CO:H2 = 2:1, 5MPa) and the reaction time was extended to 20h, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0058] Example 10 Catalyst evaluation: In Example 10, except that the syngas pressure (CO:H2 = 1:1, 5MPa) was changed to the syngas pressure (CO:H2 = 2:1, 6MPa) and the reaction time was extended to 20h, the rest of the catalyst evaluation and product analysis process was the same as in Example 1.
[0059] The reaction performance of the catalysts in Examples 1-10 above is shown in Table 1.
[0060] Table 1 Catalytic performance of Co / UiO-66-NH2-PPh3 heterogeneous catalyst under different reaction conditions As shown in Table 1, the phosphine-functionalized metal-organic framework-supported cobalt-based heterogeneous catalytic material Co / UiO-66-NH2-PPh3 prepared in this invention exhibits excellent catalytic performance. Under optimized conditions (160℃, 5MPa, 10h), it demonstrates excellent 1-octene conversion (99.9%) and total yield of aldehydes and alcohols (95.5%).
[0061] Example 11 The recycling performance of the catalyst Co / UiO-66-PPh3 from Example 1 and the catalyst Co / SBA-15-PPh2 from Comparative Example 3 was tested: the catalysts after reaction were washed and dried, and then directly used in the next cycle. Other operations and product analysis were the same as in Example 1. Reaction data for catalyst reuse are shown in [link to example]. Figure 5 .
[0062] from Figure 5As can be seen, the phosphine-functionalized metal-organic framework material supported on cobalt-based heterogeneous catalyst prepared in this invention exhibits excellent catalytic performance. After four cycles, the conversion rate of 1-octene catalyzed by Co / UiO-66-PPh3 remained at a high level, with little change compared to the initial conversion rate. Although the total yield of aldehydes and alcohols decreased slightly, the yield still reached 63% after four cycles. ICP analysis further showed that only 33% of the cobalt species leach into the liquid phase during the four cycles. In contrast, the cobalt loss rate of the catalyst Co / SBA-15-PPh2 was high, leading to a severe decline in cycle performance, proving that the phosphine coordination and MOF confinement structure of the catalyst in this invention effectively inhibited metal loss.
[0063] In Examples 12-17, the procedures were identical to those of Example 1, except that 10 mmol of a different olefin substrate was added instead of 10 mmol of octene. The reaction results for the different olefin substrates are shown in Table 2.
[0064] Table 2 Catalytic performance of catalyst Co / UiO-66-NH2-PPh3 in various olefin hydroformylation reactions in Example 1 As can be seen from the experimental results in Table 2, the phosphine-functionalized metal-organic framework material supported on cobalt-based heterogeneous catalyst prepared in this invention can be applied to the hydroformylation reaction of various olefins, and all of them exhibit good catalytic activity and yield.
Claims
1. A method for preparing a cobalt-based catalytic material supported by a phosphine-functionalized metal-organic framework, comprising the following steps: (1) Preparation of phosphine-functionalized metal-organic framework carrier materials: 2-Aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine were dissolved in N,N-dimethylformamide solvent and stirred until completely dissolved. Acetic acid was then added and mixed thoroughly. The resulting mixture was transferred to a high-pressure hydrothermal reactor lined with polytetrafluoroethylene, sealed, and reacted at 120°C for 24 hours. After the reaction was completed, the mixture was naturally cooled to room temperature. The product was separated by centrifugation and washed. The resulting pale yellow powder was dried under vacuum at 90°C to constant weight, yielding the phosphine-functionalized metal-organic framework carrier material, named UiO-66-NH2-PPh3. (2) Preparation of cobalt-based catalytic materials supported by phosphine-functionalized metal-organic frameworks: The UiO-66-NH2-PPh3 was added to a toluene solvent containing cobalt acetylacetone, stirred and ultrasonically dispersed to ensure uniformity, and then the mixture was refluxed and stirred in an oil bath at 80°C for 24 hours for loading. After the reaction was completed, the mixture was naturally cooled to room temperature, and the product was separated by centrifugation and washed. The resulting gray powder was dried under vacuum at 80°C to constant weight to obtain the phosphine-functionalized metal-organic framework supported cobalt-based catalytic material, named Co / UiO-66-NH2-PPh3.
2. The method for preparing a phosphine-functionalized metal-organic framework-supported cobalt-based catalytic material as described in claim 1, characterized in that: In step (1), the molar ratio of 2-aminoterephthalic acid, zirconium tetrachloride, and triphenylphosphine is 3:3.3:1.
5.
3. The method for preparing a phosphine-functionalized metal-organic framework-supported cobalt-based catalytic material as described in claim 1, characterized in that: In step (1), the volume ratio of acetic acid to N,N-dimethylformamide is 18:50; the ratio of 2-aminoterephthalic acid to N,N-dimethylformamide is 10.8 g / mL.
4. The method for preparing a cobalt-based catalytic material supported on a phosphine-functionalized metal-organic framework as described in claim 1, characterized in that: In step (2), the mass ratio of cobalt acetylacetone to UiO-66-NH2-PPh3 is 1:(2~3).
5. The method for preparing a phosphine-functionalized metal-organic framework-supported cobalt-based catalytic material as described in claim 1, characterized in that: In step (2), the concentration of the toluene solvent containing cobalt acetylacetonate is 3.6 mg / mL.
6. A phosphine-functionalized metal-organic framework supported cobalt-based catalytic material prepared by the preparation method according to any one of claims 1 to 5.
7. The phosphine-functionalized metal-organic framework-supported cobalt-based catalytic material as described in claim 6, characterized in that: The cobalt metal is loaded onto the UiO-66-NH2-PPh3 support in a highly dispersed form, and the theoretical loading of cobalt metal is 5 wt%.
8. The application of the phosphine-functionalized metal-organic framework supported cobalt-based catalytic material as described in claim 7 in the hydroformylation reaction of olefins.
9. The application as described in claim 8, characterized in that: The olefin is C4~C6. 12 Terminal olefins, cyclic olefins, or aromatic olefins.
10. The application as described in claim 8, characterized in that: The conditions for the hydroformylation reaction are: a reaction temperature of 80-170℃, a synthesis gas pressure of 2-6MPa, and a reaction time of 2-24h; the reaction solvent is one of toluene, DMF, dioxane, or acetonitrile; and the synthesis gas is a mixture of CO and H2 in a volume ratio of 1:1 or 1:2.